La utilización del modelo tradicional conductista en el desarrollo de la comprensión lectora de los niños de preparatoria de la Unidad Educativa Luis Telmo Paz y Miño, en el período académico 2020 - 2021. - Anchatuña Alajo, María Rosario (2021)
The present research work aims to develop lexical awareness through the use of images for reading comprehension in high school children of the “Luis Telmo Paz y Miño” Intercultural Bilingual Educational Unit in the 2020-2021 school year. The particularity of this research, allowed to influence the problems that boys and girls present in reading comprehension, for this innovative activities were proposed that allowed to improve the quality of teaching, designing a guide of methodological strategies for the resolution of the indicated problem. It is a descriptive study because it describes the teaching methodology in the acquisition of reading comprehension and lexical awareness skills in high school boys and girls, it has a qualitative and quantitative approach, it is cross-sectional. To obtain the information, different instruments were applied such as: surveys applied to teachers and parents of the institution, a checklist to see the progress of reading comprehension in children. From this perspective, the main purpose of this research is to implement a didactic guide of activities in order to offer a pedagogical and didactic tool to teachers, students and parents, which facilitates their educational work, optimizes time and their time develop in each of the students lexical awareness, which is essential to improve reading comprehension. After having carried out the corresponding analysis, it was obtained as a result that 96% of the students have achieved the required learning (A). Therefore, it is concluded that reading comprehension strategies responded to the needs and interests of each of the children, allowing them to be able to make value judgments, solve their own problems and contribute to society.